The Interaction of Mortgage Credit and Housing Prices in the US - Fabian Lindner (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
This paper looks at the relation between mortgage credit and housing values. It has become conventional wisdom in policy circles that credit growth led to the housing bubble in the US. However, this statement has not been empirically tested as of yet. The paper uses the Johansen procedure to estimate a long run relationship between mortgage credit and housing prices between 1984 and 2012 and analyzes the interactions between the variables. To this effect, two models with two different housing price variables are estimated. It is found that mortgage credit is weakly exogenous. Impulse-response functions, variance decompositions and out of sample forecast also show that mortgage credit drives housing prices and not vice versa. The paper also looks at the effect of short-term and long-term interest rates and does not find important influences of both on housing prices or mortgage credit. The role of monetary policy is not likely to have been very strong in the built-up of the housing bubble.
urn:nbn:de:101:1-2014052213349
Keywords: E22; E44; E52; G21; 330; Housing Prices; Mortgage Markets; Monetary Policy